Income mobility - Markus Jäntti; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We survey the literature on income mobility, aiming to provide an integrated discussion of mobility within and between generations. We review mobility concepts, descriptive devices, measurement methods, data sources, and recent empirical evidence.
Keywords: D31; I30; 330; Intragenerational mobility; intergenerational mobility; income mobility; earnings mobility